2017
DOI: 10.1016/j.actaastro.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

How far are extraterrestrial life and intelligence after Kepler?

Abstract: The Kepler mission has shown that a significant fraction of all stars may have an Earth-size habitable planet. A dramatic support was the recent detection of Proxima Centauri b. Using a Drake-equation like formalism I derive an equation for the abundance of biotic planets as a function of the relatively modest uncertainty in the astronomical data and of the (yet unknown) probability for the evolution of biotic life, F b . I suggest that F b may be estimated by future spectral observations of exoplanet biomarke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Recent data of the Kepler mission show that 10-50% of the M-dwarfs have small planets orbiting within their habitable zone (Batalha et al 2013;Dressing and Charbonneau, 2015), which implies that such planets could be found within less than 10 light years from Earth (Wandel, 2015;2017a). A high abundance of Earth-size volatile-rich planets close to low mass M-stars is also supported by theoretical arguments and planetary formation models (Alibert and Benz 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data of the Kepler mission show that 10-50% of the M-dwarfs have small planets orbiting within their habitable zone (Batalha et al 2013;Dressing and Charbonneau, 2015), which implies that such planets could be found within less than 10 light years from Earth (Wandel, 2015;2017a). A high abundance of Earth-size volatile-rich planets close to low mass M-stars is also supported by theoretical arguments and planetary formation models (Alibert and Benz 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With this assumption the average distance db between biotic neighbor planets can be shown to be (Wandel 2015;2017) db ~ 3 (n* FsFEHZ Fb) -1/3 pc (14) where n* is the stellar number-density in the solar neighborhood.…”
Section: The Cosmic Abundance Of Lifementioning
confidence: 99%
“…While some authors point out some disadvantages for the evolution of life on planets orbiting M-type stars, such as high levels of XUV radiation and stellar winds, which may cause atmosphere erosion (Heller, Leconte and Barnes 2011;Leconte, Wu, Menou and Murray 2015, Lingam and Loeb 2017, Tilley et al, 2019, other works argue that such planets may nevertheless host life as we know it (e.g. Tarter et al, 2007, Gale andWandel 2017). They point out that the impact of the high XUV flux received by planets orbiting in the habitable zone of young M-type hosts may be less important for aquatic life.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters, are now believed to be of order unity (e.g. Batalha et al 2013;Dressing and Charbonneau, 2015;Wandel 2017). Our main ignorance remains in the last three terms: (i) the chances for the evolution of biological life; (ii) the probability of intelligence; and (iii) the lifespan of a technological communicating civilization.…”
Section: Introductionmentioning
confidence: 99%